The validity of the Ligs digital arthrometer at different loads to evaluate complete ACL ruptures - Li, Junqiao; Tang, Jiexi; Yao, Lei; Fu, Weili; Deng, Qian; Xiong, Yan; Li, Jian (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: The Ligs Digital Arthrometer is a recently launched versatile arthrometer that can be used for the quantitative assessment of knee and ankle joint laxity. This study aimed to evaluate the validity of the Ligs Digital Arthrometer for the diagnosis of complete anterior cruciate ligament (ACL) ruptures at different loads. Materials and Methods: From March 2020 to February 2021, we included 114 normal subjects and 132 subjects diagnosed with complete ACL ruptures by magnetic resonance imaging (MRI) and eventually confirmed by arthroscopy in the study. Anterior knee laxity was independently measured by the same physical therapist using the Ligs Digital Arthrometer. Recorded anterior knee laxity and calculated the side-to-side difference (SSD) at 30, 60, 90, 120, and 150 N loads, respectively. The receiver operating characteristic (ROC) curve was used to determine the optimal laxity threshold, and the diagnostic value was evaluated by the area under the curve (AUC). Results: The demographic data of the subjects were comparable between the two groups (p > 0.05). The mean values of anterior knee laxity measured by the Ligs Digital Arthrometer between the complete ACL ruptures group and the control group were significantly different at 30, 60, 90, 120, and 150 N loads (p < 0.001 for all). According to the results of ROC curve analysis, the optimal laxity threshold for the diagnosis of complete ACL ruptures was 1.1 mm SSD (Se = 66.7%, Sp = 69.3%) at 30 N, 1.3 mm (Se = 74.2%, Sp = 82.5%) at 60 N, 1.6 mm (Se = 79.5%, Sp = 94.7%) at 90 N, 1.9 mm (Se = 84.1%, Sp = 92.1%) at 120 N and 2.1 mm (Se = 85.6%, Sp = 91.2%) at 150 N. The AUC order at different loads from high to low was 150 N (0.948 [0.923–0.973])>120 N (0.933 [0.903–0.963])>90 N (0.902 [0.862–0.943])>60 N (0.846 [0.799–0.893])>30 N (0.720 [0.657–0.783]). Conclusion: The Ligs Digital Arthrometer proved to be of high diagnostic value in complete ACL ruptures at 90 N, 120 N, and 150 N loads. The diagnostic value improved with the increase of load in a certain range. Based on the results of this study, as a portable, digital and versatile new arthrometer, the Ligs Digital Arthrometer was a valid and promising tool for diagnosing complete ACL ruptures.